Analisis Efektivitas Mediasi dalam Penyelesaian Sengketa Bisnis melalui Pendekatan Studi Kasus Empiris - Andi Wirawan; Natasya Kartika (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The increasing complexity of business disputes in Indonesia highlights the limitations of litigation as a mechanism for achieving efficient and equitable resolution. Mediation has emerged as a viable alternative; however, its effectiveness within Indonesia’s legal system remains inconsistent. This study aims to analyze the effectiveness of mediation in resolving business disputes by identifying the factors influencing success and evaluating institutional performance. Using an empirical legal research approach, data were obtained from 15 respondents, including mediators, business actors, and legal practitioners, complemented by case analysis from 2020 to 2023. The findings indicate that the average mediation success rate in Indonesia is 11.4%, while satisfaction among disputing parties reaches 73%, suggesting high procedural efficiency but limited substantive outcomes. Furthermore, 70% of practitioners acknowledge that institutional capacity and mediator competence significantly affect settlement success, and cases with high economic value tend to experience negotiation deadlocks. Comparative analysis shows that Indonesia’s mediation framework lags behind countries such as Singapore and Japan in terms of enforcement consistency and professional regulation. This study contributes to legal scholarship by emphasizing that mediation effectiveness depends not only on formal legal frameworks but also on institutional credibility and cultural trust. The novelty of this research lies in its empirical demonstration of the gap between procedural efficiency and substantive justice in Indonesia’s mediation system, providing insights for strengthening alternative dispute resolution mechanisms within the evolving digital economy.